Perbandingan Struktur Histologi Magnum pada Itik Magelang, Itik Tegal dan Itik Pengging - Yuriwati, Febry Nurmala; Mardiati, Siti Muflichatun; Tana, Silvana (BULETIN ANATOMI DAN FISIOLOGI dh SELLULA, 2016)
Duck is one of comodity in livestock which its productivity needs to be improved. The duck productivity is related to physiological function of the reproductive ogans. Magelang ducks, Tegal ducks and Pengging ducks have the potential to be developed. This research was aimed for comparing magnum hystology structure among Magelang Duck, Tegal Duck, and Pengging Duck. There were six ducks on each breed and at the age of six months old taken from breeding and cultivation ofnon-ruminant livestock, Banyubiru, regency Ambarawa, Used parafin method by Hematoxylin and Eosin staining. The data of magnum histology structure of magelang duck, tegal duck, and pengging duck that descriptively analyzed with captured and microscopic observation at first. Data of long reproductive tract, reproductive tract weight and ovarian weight were analyzed by using Analysis of Varian (ANOVA), by a further test ofÂ  Least Significant Differences (LSD) test at the level of 95%. Data analized of long reproductive tract, reproductive tract weight and ovarian weight did not show the significant difference. The histological structure on Magelang duck, Tegal duck and Pengging duck showed epithelial cells differentiated into ciliated epithelial cells and goblet cells and sub epithelial gland that had developed. It was concluded the magnum histological structure its not difference on Magelang ducks, Tegal ducks and Pengging ducks on 6 months old. Â  Keywords: local duck, histology, magnum